2022
DOI: 10.1055/a-1825-9641
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 in Bone Metabolism: Basic and Clinical Aspects

Abstract: The use of standard procedures for the diagnosis of osteoporosis and assessment of fracture risk significantly decreased during the COVID-19 pandemic, while the incidence of fragility fractures was mostly unaltered. Both COVID-19 per se and its treatments are associated with a negative impact on bone health. Preclinical models show that mice infected with SARS-CoV2 even without symptoms display loss of trabecular bone mass two weeks post infection, due to increased numbers of osteoclasts. Osteoporosis medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…During the pandemic, a substantial drop in the treatment of apparent osteoporosis and adherence to medication has been seen, thereby increasing the likelihood of non-traumatic fractures due to further bone demineralization [24]. The overall reduction in medical consultations during the pandemic has led to significant delays and decreases in the diagnosis and treatment of osteoporosis [25]. Additionally, the COVID-19 infection has been linked to a loss of trabecular mass through overexpression of osteoclasts, as seen in mouse models [26].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, a substantial drop in the treatment of apparent osteoporosis and adherence to medication has been seen, thereby increasing the likelihood of non-traumatic fractures due to further bone demineralization [24]. The overall reduction in medical consultations during the pandemic has led to significant delays and decreases in the diagnosis and treatment of osteoporosis [25]. Additionally, the COVID-19 infection has been linked to a loss of trabecular mass through overexpression of osteoclasts, as seen in mouse models [26].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These patients have been associated with low serum calcium levels 4 and decreased bone mineral density. 5 It has been suggested that the effects of COVID-19 on bone metabolism may negatively affect the osteointegration of dental implants. 2,3 Dental implant failures are classified as late or early failures based on the time of occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…When coronavirus interferes with the ACE‐2 receptor, it changes the osteoclast/osteoblast balance in favor of osteoclasts, leading to bone resorption 2,3 . These patients have been associated with low serum calcium levels 4 and decreased bone mineral density 5 . It has been suggested that the effects of COVID‐19 on bone metabolism may negatively affect the osteointegration of dental implants 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…In past studies, scientists had suggested that the development of osteoporosis is not directly related to pneumonia. However, many studies indicated that bone metabolism disorder, bone mineral density decreasing, and bone microarchitecture destruction occurred in patients infected with SARS-CoV2 during the last 3 years of the COVID-19 pandemic ( Mi et al, 2021 ; Tsourdi et al, 2022 ). COVID-19 increased the fragility of bone tissue and the risk of fractures with increasing severity ( Battisti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%